Network fundamentals : CCNA exploration companion guide - Dye, Mark; McDonald , Rick ;Rufi, Antoon W. (Indianapolis, Indiana : Cisco Press, 2008)
"Network Fundamentals, CCNA Exploration Companion Guide is the official supplemental textbook for the Network Fundamentals course in the Cisco Networking Academy CCNA Exploration curriculum version 4. The course, the first of four in the new curriculum, is based on a top-down approach to networking. The Companion Guide, written and edited by Networking Academy instructors, is designed as a portable desk reference to use anytime, any where. The book's features reinforce the material in the course to help you focus on important concepts and organize your study time for exams."--BOOK JACKET.
Ch. 1. Living in a Network-Centric World -- Ch. 2. Communicating over the Network -- Ch. 3. Application Layer Functionality and Protocols -- Ch. 4. OSI Transport Layer -- Ch. 5. OSI Network Layer -- Ch. 6. Addressing the Network: IPv4 -- Ch. 7. OSI Data Link Layer -- Ch. 8. OSI Physical Layer -- Ch. 9. Ethernet -- Ch. 10. Planning and Cabling Networks -- Ch. 11. Configuring and Testing Your Network -- App. Check Your Understanding and Challenge Questions Answer Key -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: ELECTRONIC DATA PROCESSING PERSONNEL -- CERTIFICATION